Optimization of layout of the large-size wind turbines with horizontal axis in the wind farm - Alireza SHirzadegan, Reza Aghaei Togh (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
The purpose of the study was to provide the best layout of large-size wind turbines so that the highest efficiency could be attained from wind turbines or in other words, the maximum electricity would be generated in a wind farm. The study first examined a single wind turbine and then three wind turbines together. Moreover, V-47 660 KW wind turbine was selected for the study according to the analyses performed. This study was done numerically in CFX software. The study also used the blade element method (BEM). It has to be noted that the BEM theory was used for aerodynamic calculations of wind turbine blades. Finally, according to the information obtained from the analysis of these three wind turbines together and the output power extracted from these turbines, the best layout of wind turbines in a wind farm was obtained. If this layout is used in wind farms the most power generated from wind turbines can be obtained.